AVR Microcontroller Implementation for Customized Sound Generation - Tanvir Hussain; Md Mejbaul Haque (Institute of Advanced Engineering and Science, 2012)
In this paper, we have proposed a technique by which customized sound can be generated using 8 bit AVR microcontroller. Any sound file chosen from computer can be integrated in microcontroller programming which is written in C and compiled by AVR libc compiler. An 8 bit DAC connected to PORT A of AVR microcontroller takes data of sound file as input and gives converted analog sound signal as output. An audio amplifier based on LM386 Op-Amp circuit amplifies the sound signal which is finally connected to 8Ω speaker for audible sound output. This circuit has been simulated using Proteus ISIS 7 Virtual System Modeling (VSM).DOI:http://dx.doi.org/10.11591/ijece.v2i1.139